Effect of derivative cutting on machining performance of micro textured tools. (September 2019) - Duan, Ran; Deng, Jianxin; Lei, Shuting; Ge, Dongliang; Liu, Yayun; Li, Xuemu
Highlights: Derivative cutting of micro-textured tools refers to the additional cutting to the bottom side of the chip with the micro-surface textures on the tool surface. The research of derivative cutting is still at its early stages, and it is especially in need of experimental studies. Derivative cutting occurs in machining with the micro textured tool, contributing to the changes of cutting forces, tool wear, and chip formation. Based on the experimental results, the inhibition strategies for derivative cutting from the previous theoretical studies are improved. Abstract: Derivative cutting often happens when micro textures perform cutting action on the chip bottom side, which hinders the effectiveness of micro textured tools in dry machining. The effects of derivative cutting on machining performance need to be comprehensively studied in terms of cutting forces, tool wear and chip formation. Dry cutting tests on AISI H13 steel were carried out using the micro textured tools (TT) and conventional tools (CT) over a range of cutting velocities from 95 to 237 m/min. Results show that the derivative cuttings occurred during machining with the TT tools in this range of cutting velocity. The effects of derivative cutting are analyzed based on the results and reflected in the following observations. On the one hand, derivative cutting can generate a great deal of heat on the textured rake face, increasing cutting temperature. On the other hand, derivative cutting can produce intensive material removal and plowing action on the chip bottom side, increasing cutting force. Overall, derivative cutting can accelerate texture wear, which in turn aggravates derivative cutting. This leads to a severer tool-chip friction, which should be minimized when machining with textured cutting tools.